(untitled) (Jurnal Teknologi Industri Pertanian, 2023)
White frangipani flowers (Plumeria obtusa) are widespread across many regions in Indonesia and are frequently used as an essential component of religious ceremonies as offerings in the temples. They can be found placed at many village corners as local culture and beliefs. The used frangipani flowers caused a huge amount of flower waste. To resolve this issue, frangipani flowers can be utilized through product development to add their value, such as by producing essential oils. It has been reported from previous studies that the essential oil of frangipani flowers was done through conventional methods which used toxic chemical solvents or distillation processes with high-temperature conditions that can damage the volatile and bioactive compounds in flowers. Thus, in this research, the processing of frangipani flowers into essential oil was done with supercritical carbon dioxide (CO2) extraction. The results showed that supercritical CO2 extraction produces a lower yield (1.27%) of essential oil if compared to soxhlet extraction with n-hexane (4.23%), however supercritical CO2 extraction provides advantages of no residue of extraction product and more environmentally-friendly method. Furthermore, the identification of bioactive compounds from P. obtusa essential oil showed that there were 65 compounds identified from supercritical CO2 extraction with 87% of compounds with activities and benefits reported from literature, whereas essential oil from soxhlet extraction produced more compounds, 76 compounds were identified with 78% of compounds with reported activities and benefits. This confirms that supercritical CO2 extraction was more selective in extracting specific volatile compounds. Keywords: bioactive, carbon dioxide, essential oil, plumeria obtuse, supercritical fluid extraction